2004
DOI: 10.1097/01.shk.00001276869.21260.9d
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Attenuates the Tissue Injury Associated With Hemorrhagic Shock and Myocardial Ischemia

Abstract: Here we investigate the effects of erythropoietin (EPO) on the tissue/organ injury caused by hemorrhagic shock (HS), endotoxic shock, and regional myocardial ischemia and reperfusion in anesthetized rats. Male Wistar rats were anesthetized with thiopental sodium (85 mg/kg i.p.) and subjected to hemorrhagic shock (HS; i.e., mean arterial blood pressure reduced to 45 mmHg for 90 min, followed by resuscitation with shed blood for 4 h), endotoxemia (for 6 h), or left anterior descending coronary artery occlusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 29 publications
3
106
0
Order By: Relevance
“…Thus, our in vivo findings support the view that EPO directly protects cells by preventing activation of the apoptosis pathway. In support of this concept, Abdelrahman and colleagues have demonstrated that EPO also reduces the activation of caspase 3 caused by severe hemorrhage and resuscitation of the kidney, by inhibiting the activation of the caspase cascade via prevention of both the mitochondrial caspase 9 pathway and death receptor-mediated activation of caspase 8 (51).…”
mentioning
confidence: 91%
“…Thus, our in vivo findings support the view that EPO directly protects cells by preventing activation of the apoptosis pathway. In support of this concept, Abdelrahman and colleagues have demonstrated that EPO also reduces the activation of caspase 3 caused by severe hemorrhage and resuscitation of the kidney, by inhibiting the activation of the caspase cascade via prevention of both the mitochondrial caspase 9 pathway and death receptor-mediated activation of caspase 8 (51).…”
mentioning
confidence: 91%
“…Antiapoptotic and tissue protective effects of EPO have been demonstrated most vigorously in models of ischemia-reperfusion injury affecting the brain, intestine, heart, and kidney, among other organs and tissues (14,(24)(25)(26). More recently, studies have indicated that EPO has cytoprotective effects in experimental models of inflammation and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…EPO, a hematopoietic growth factor with antiapoptotic properties, has been shown to have cytoprotective effects in various organs and tissues (14,15,17). We previously demonstrated that EPO attenuates splenic and thymic apoptosis in an endotoxic sepsis model (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64][65][66] Of these, one study reported a positive outcome with another treatment being compared with EPO, 65 and one study reported contrasting positive effects of EPO using a different model of AKI. 64 These data likely reflect the strong and persistent publication bias for reporting only positive outcomes of studies throughout the medical literature.…”
Section: Preclinical Study Design and Reportingmentioning
confidence: 99%